Exploring Teachers’ Technological Knowledge in English Languange Teaching Practice - Nila Irmayani Irma; Chairil Anwar Korompot; Fitriyani (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
Educational technology is essential for creating interactive, effective, and student-centered learning. However, based on recent national data, the use of educational technology by teachers in Indonesia is still relatively low. The Ministry of Education and Culture (2021) found that only around 30% of teachers actively use digital platforms to support learning on a regular basis. This low usage is partly due to varying digital skills and confidence levels among teachers, which can limit the effective integration of technology in classrooms. This study aims to determine teachers’ technological knowledge in English language teaching within the TPACK framework, including the kinds of technology used, and how teachers apply technology in classroom practices. The type of research used in this study is qualitative approach with a narrative inquiry design. The subjects of this research are English teachers at a junior high school in Mangkoso who teaches English. The findings of the study indicate that teachers’ technological knowledge about teaching English at junior high school in Mangkoso are demonstrated through the ability to operate several digital tools and integrate them into classroom activities. Teachers used Smart TVs, laptops, tablets, projectors, Kahoot, Quizizz, Ruang Guru, Word wall, YouTube, PowerPoint, and AI tools. Teachers effectively practiced technological knowledge by selecting and customizing digital tools, presenting videos and audio, creating learning materials, and designing technologybased activities that actively support teaching English. The meaning of these findings is interpreted based on the classroom situation and the teaching context. This study is beneficial for supporting technology based English learning and can contribute to improving the implementation of the TPACK framework in schools.